B325 Accurate delivery of local anaesthetic via rectus sheath catheters. (11th August 2022) - Ho, G; Yarr, C; Merjavy, P
Abstract : Background and Aims: Rectus sheath blocks (RSB) have been used for abdominal analgesia for many years. Local anaesthetic administered to the posterior rectus sheath plane blocks terminal branches of T7–11 intercostal nerves. Therefore the RSB provides somatic analgesia for midline abdominal incisions. Whilst a single shot technique is common, rectus sheath catheters may be placed to deliver either a continuous infusion or intermittent boluses of local anaesthetic for prolonged analgesia. We tested the rectus sheath catheter set (Pajunk, Germany) to observe whether equal volumes of local anaesthetic are delivered to the left and right catheters. Methods: We have created a bench top collecting apparatus connected to 0.9% sodium chloride in place of local anaesthetic. The pump was programmed to deliver our local protocol of 40 ml boluses 4 hourly. After 24 hours the volume in each collecting bottle was measured by digital weighing scales. This process was repeated 10 times, with a new catheter set each time. Results: We found that after 24 hours the intended 6 boluses delivered equal volumes to both right and left catheters. The overall volume delivered compared to the volume registered by the pump showed a small discrepancy of 2 mls over 24 hours. Conclusions: In conclusion under test conditions the rectus sheath catheter set delivers equal volumes to each side. This may improve confidence that local anaesthetic delivery to rectus sheath or erector spinae plane blocks via this catheter is equal. However, differences in resistance may exist under clinical conditions. This was not tested, but may be an opportunity for further investigation.